1990
DOI: 10.1139/t90-059
|View full text |Cite
|
Sign up to set email alerts
|

The effects of plugging on pile performance and design

Abstract: During installation of open-pipe piles, soil enters the pile until the inner-soil cylinder develops sufficient resistance to prevent further soil intrusion and the pile becomes "plugged." In spite of its frequent occurrence, only limited attention has thus far been given to this phenomenon and its consequences. The effects of plugging on pile performance and design are examined in reference to the following aspects: ultimate static capacity, time-dependent pile capacity, and dynamic behavior. Pile plugging is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 0 publications
2
44
0
4
Order By: Relevance
“…The unit base resistance (q b = base load/base area) developed by an open-ended pile is generated by two components; namely the annular stress (q ann ) mobilized beneath the pile wall and the plug stress (q plug ) which is controlled by the internal shear stresses which develop between the soil plug and pile wall (Paikowsky and Whitman 1990) Figure 17, the horizontal coefficient of consolidation was taken as the average value determined from piezocone dissipation tests, of 9.5 m 2 /year.…”
Section: Base Resistance During Installationmentioning
confidence: 99%
“…The unit base resistance (q b = base load/base area) developed by an open-ended pile is generated by two components; namely the annular stress (q ann ) mobilized beneath the pile wall and the plug stress (q plug ) which is controlled by the internal shear stresses which develop between the soil plug and pile wall (Paikowsky and Whitman 1990) Figure 17, the horizontal coefficient of consolidation was taken as the average value determined from piezocone dissipation tests, of 9.5 m 2 /year.…”
Section: Base Resistance During Installationmentioning
confidence: 99%
“…As the driving depth increases, the IFR tends to drop, and a depth may be reached beyond which driving will proceed in the fully plugged mode. The IFR also decreases with decreasing pile diameter for the same pile driving depth (Paikowski and Whitman 1990). The decreasing IFR values with increasing driving depth may be explained by the formation of the wedged and unwedged soil plug lengths.…”
Section: Estimation Of Ifr For Open-ended Pilesmentioning
confidence: 81%
“…The plug development of all three piles was similar, reflecting the consistent installation procedure used. Paikowsky and Whitman (1990) conducted a comprehensive study of plug development, and noted that the plugging behaviour of driven piles was difficult to predict. However, it was observed that during quasi-static penetration, which occurs during free run (at the start of installation, when the pile penetrates under selfweight), piles became fully plugged within a penetration of 10-20 pile diameters in a range of soil types from soft to stiff clay.…”
Section: Plug Developmentmentioning
confidence: 99%